Jewish Communities of the World
IX, 206 p.
Keywords: This fourth edition attempts to provide an up-to-date and comprehensive guide to Jewish life and institutions in 98 national communities worldwide. Entries include a brief historical outline and sections on legal status, communal organizations, religious life, education and welfare.